Application of Al-Wujuh Wa An-Nazhair Rules and Tafsiriyah Tarjamah on Human Words in the Translation of the Ministry of Religion of the Republic of Indonesia - Siti Ersa Meylani; Kharis Nugroho; Abdullah Mahmud; Mutohharun Jinan; Trisno Susilo; Andri Nirwana AN (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This research discusses a study of the rules of al-wujūh wa an-naẓāir in the tarjamah tafsiriyah regarding the word human in the Ministry of Religion's translation of the Koran. The verses of the Qur'an that were revealed in Arabic have many unique words and a variety of meanings according to the context of the verses, so it is necessary to study the meaning of these words to make it easier for Muslims to understand the verses. The rules of al-wujūh wa an-naẓāir are a study of the science of the Qur'an which discusses meaning and pronunciation. The spread of Muslims outside the Arab nation requires the translation of verses of the Qur'an into their native languages. There are two translation methods, namely literal translation and tafsiriyah translation. By formulating how to apply al-wujūh wa an-naẓāir and tarjamah tafsiriyah of the word human in the Qur'an, researchers used the maudhu'I method and a descriptive qualitative approach. The results of the research are that the mention of humans in the Qur'an is Basyar, Insan, Nas, Bani Adam with the same meaning.